Molybdenum disulfide for ultra-low detection of free radicals: electrochemical response and molecular modeling. (28th April 2017) - Gupta, Ankur; Rawal, Takat B; Neal, Craig J; Das, Soumen; Rahman, Talat S; Seal, Sudipta
Abstract: Two-dimensional (2D) molybdenum disulfide (MoS2 ) offers attractive properties due to its band gap modulation and has led to significant research-oriented applications (i.e. DNA and protein detection, cell imaging (fluorescent label) etc.). In biology, detection of free radicals (i.e. reactive oxygen species and reactive nitrogen (NO * ) species are very important for early discovery and treatment of diseases. Herein, for the first time, we demonstrate the ultra-low (pico-molar) detection of pharmaceutically relevant free radicals using MoS2 for electrochemical sensing. We present pico- to nano- molar level sensitivity in smaller MoS2 with S-deficiency as revealed by x-ray photoelectron spectroscopy. Furthermore, the detection mechanism and size-dependent sensitivity have been investigated by density functional theory (DFT) showing the change in electronic density of states of Mo atoms at edges which lead to the preferred adsorption of H2 O2 on Mo edges. The DFT analysis signifies the role of size and S-deficiency in the higher catalytic activity of smaller MoS2 particles and, thus, ultra-low detection.